158 Myocardial work exposes afterload-dependent changes in strain. (17th January 2020) - Sletten, O J; Aalen, J; Khan, F H; Larsen, C K; Inoue, K; Remme, E W; Hisdal, J; Smiseth, O A; Skulstad, H
Abstract: Funding Acknowledgements: Norwegian Health Association Background: Global longitudinal strain (GLS) is used for detection of subclinical left ventricular (LV) dysfunction, for example when screening for chemotherapy-induced cardiotoxicity. A relative percentage reduction in GLS ≥8% is considered abnormal. However, as GLS is load-dependent, modest increases in afterload can potentially prove sufficient to cause clinical implication. In contrast, global myocardial work (GMW) which incorporates afterload, may be more accurate in detecting LV-dysfunction. Purpose: We investigated the effect of increased afterload on GLS, and if GMW may be a more accurate parameter of myocardial function during increased afterload. Methods: In 20 healthy individuals (age 49 ± 11 years (mean ± SD), 10 men), blood pressure was increased by a 3 minute arithmetic mental stress test. GLS was measured by speckle tracking echocardiography and LV ejection fraction (EF) by biplane Simpson. GMW was calculated from LV pressure-strain analysis using a non-invasive estimate for LV pressure (LVP). Results: During the afterload-elevation, systolic blood pressure increased by 25 ± 16 mmHg (p < 0.01), and heart rate by 16 ± 13 bpm (p < 0.01). This was followed by a decrease in EF from 62 ± 5 to 59 ± 5% (p < 0.01) and GLS from 21.9 ± 2.2 to 20.8 ± 2.0% (p < 0.01). In contrast, GMW increased from 2052 ± 278 to 2382 ± 388 mmHg·% (p < 0.01). In 5 of 20 (25%) individuals, the relative percentage reduction of GLS was >8%, despite an increase in GMW. The figure shows an individual example during rest and afterload-elevation, where an increase in systolic blood pressure of 16 mmHg was associated with a 9% relative percentage reduction in GLS, but a small increase in GMW as illustrated by the loop areas. Conclusions: This study demonstrated that a modest increase in afterload can result in significant reduction in GLS, that may lead to overdiagnosis of LV-dysfunction. GMW did not decrease, suggesting it has a better specificity in patients at risk for subclinical LV dysfunction. Future studies should investigate if GMW is more accurate than strain in detecting LV-dysfunction.